Changing Identities to Change the World: Identity Motives in Lifestyle Politics and Its Link to Collective Action. Issue 5 (6th February 2018) - Fernandes‐Jesus, Maria; Lima, Maria Luísa; Sabucedo, José‐Manuel
Abstract : In this article, we assume an interdisciplinary approach to the study of why and how people transpose political considerations to their lifestyles. Our aims are threefold: to understand the meanings and perceptions of people engaged in lifestyle politics and collective action; to examine the motives guiding individual change; and to explore the linkage processes between lifestyle politics and collective action. Identity process theory is considered as a lens to examine the processes and the motives of identity via a thematic analysis of 22 interviews. This study combined interviews with people seeking social change through their lifestyles with interviews with members of action groups and social movements. We found that each participant's identity is guided by identity motives such as distinctiveness, continuity, and psychological coherence. Besides, lifestyle politics is evaluated as an effective way to bring about social change, depending on the individual experience of perceived power to bring about change through collective action. Overall, lifestyle politics states the way in which the participants decided to live, to construct their identities, and to represent their beliefs about the right thing to do. Lifestyle politics complements collective action as a strategy to increase the potential of bringing about social change. The implications of this research are discussed in relation to the importance of understanding the processes of identity and lifestyle change in the context of social, environmental, and political change.